2007
DOI: 10.1200/jco.2007.11.5287
|View full text |Cite
|
Sign up to set email alerts
|

Antimetabolite Radiosensitizers

Abstract: Radiosensitization with antimetabolites has improved clinical outcome for patients with solid malignancies, especially cancers of the GI tract, cervix, and head and neck. Fluorouracil (FU) and hydroxyurea have been widely used clinically during the last four decades, and promising results have been observed more recently with gemcitabine. Although the antimetabolites all target DNA replication, they differ with respect to the mechanisms by which they produce radiosensitization. The antimetabolite radiosensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 79 publications
1
70
0
2
Order By: Relevance
“…In these studies, however, we exploited a new opportunity to use similarly low, clinically achievable levels of MTX (,10 mmol/L) to enhance the radiosensitivity of breast cancer cells to 111 In-NLS-trastuzumab. The differential sensitivity of breast cancer cells to MTX was not further assessed, but antimetobolites are among the most potent radiosensitizers and are often active at concentrations below those necessary to induce cytotoxicity (35). Indeed, other studies have demonstrated that the efficacy of Auger electron radiotherapy can be significantly enhanced by MTX.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, however, we exploited a new opportunity to use similarly low, clinically achievable levels of MTX (,10 mmol/L) to enhance the radiosensitivity of breast cancer cells to 111 In-NLS-trastuzumab. The differential sensitivity of breast cancer cells to MTX was not further assessed, but antimetobolites are among the most potent radiosensitizers and are often active at concentrations below those necessary to induce cytotoxicity (35). Indeed, other studies have demonstrated that the efficacy of Auger electron radiotherapy can be significantly enhanced by MTX.…”
Section: Discussionmentioning
confidence: 99%
“…PMX has been used in combinations with gemcitabine, tyrosine kinase inhibitors, antibodies, or even external radiation (22)(23)(24). A combination of PMX with external radiotherapy was based on the observation that PMX acts as a radiosensitizing agent in variable types of cancer cells in vitro and in vivo (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Radiosensitizers, which are currently receiving increasing amounts of attention, primarily include the following categories: 1) electrophilic radiosensitizers, represented by misonidazole and its derivatives; 2) biological reductants, namely hypoxic cytotoxic drugs; 3) chemotherapy drugs such as platinum, 5-fluorouracil, gemcitabine, taxol, camptothecin, and vinca alkaloids; antimetabolites such as gemcitabine act on cells during S-phase, and they can also prevent the progression of cells in the G1-phase to the S-phase, affect cell cycle redistribution, and inhibit the radioactive damage repair of cellular DNA (Shewach and Lawrence, 2007); 4) molecular targeted drugs such as epidermal growth factor receptor inhibitors including cetuximab and erlotinib, as well as the cyclooxygenase-2 inhibitor celecoxib (Katz et al, 2009;Herman et al, 2013); and 5) natural medicines such as irisquinone. An ideal radiosensitizer should possess the following characteristics (Kvols et al, 2005): 1) stability; it should not react easily with other substances in vivo, but exhibit a slow metabolic degradation and a long biological half-life; 2) the ability to selectively concentrate in the tumor tissue; 3) the effective therapeutic dose must be below the toxic dose; 4) some solubility in water or fat; 5) the ability to selectively sensitize hypoxic cells while having little or no effect towards normal aerobic cells; 6) no demonstration of phase-dependent characteristics, i.e., it should ideally function throughout the cell cycle.…”
Section: Discussionmentioning
confidence: 99%